Religious Doctrine Construction and Piety Control: An Analysis of Discipline among State Civil Servants in Palembang Government - Muhammad Amin; Ambar Sari Dewi; Sekar Ayu Aryani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study examines the role of power and religion in disciplining State Civil Servants (ASN) in the Palembang City Government, South Sumatra Indonesia, by taking the case of the Fajr Congregational Prayer Movement. The study is relevant due to the widespread indiscipline practices among Indonesian State Civil Servants and the use of religious approach to ASN’s disciplinary. Using qualitative research approach, data in this study obtained through in-depth interviews with government officials, ASN, and religious leaders; and content analysis of online news, Facebook, and Instagram posts. Foucault’s theory of disciplinary mechanisms was applied as analytical framework. Results of this study showed that the Government integrated religious doctrine and piety control as disciplinary instruments. This approach introduces a new dynamic in monitoring civil servant behaviour, differing from conventional bureaucratic practices. The research offers a new perspective on the relationship between power, religion, and bureaucracy while enriching discussions on variations in disciplinary mechanisms within the context of a majority Muslim country. The findings also suggest avenues for further research on the effectiveness of religious approaches in bureaucratic reform.